Já li muita coisa, então, eu posso inventar mais! A leitura literária e o desenvolvimento do pensamento criativo na infância - Faria, Kivia Pereira de Medeiros (2014)
This study investigates the contributions of reading literature for the development of creative thinking in childhood. Its relevance consists in exploring practices that contemplate the creative thinking development in apprentices at school space and understanding the literature like a significant way to promote the creative thinking. The study is connected to the qualitaty strand. The exploratory observation and the intervention were adopted as research techniques. The field diary and the audio and video recording of the reading sections were adopted as methodological instruments. The research was conducted in the application s college from the Federal University of Rio Grande do Norte, in a 1th grade class, with 18 students between 6 and 7 years old. During the intervention, 8 readind class happened, with varied strategies and literary genres. The reading sessions were conducted through the principles of scaffolding, defended by Graves and Graves (1995). The corpus is made of speaks episodes, whose encoding semantics allowed the grouping into two central categories: divergent thinking and coauthoring of literary reader. It was taken as a theoretical framework the studies of Amarilha (2011; 2006; 2001; 1991; 1993; 1994), Alencar (2001), Coelho (2000; 1997), Culler (1999), De Masi (2005), Gallo (2000), Guilford (1977), Iser (1996), Jouve (2002), Kneller (1978), Martínez (1997), Smith (2003), Stierle (1979), Vigotski (2009; 1998), Wechsler; Nakano (2003; 2002). The analysis points to the formation of creative individuals in the classroom, through the reading of literature. Reposition the literary education front of the new social demands. Resizes the function of school in children s development, considering the children s skill in exploring, testing hypotheses and making use of their creative thinking, in climate of freedom mental. It signals, in this way, the teacher like a mediator, promoting a favorable to the development of creative thinking environment, a stimulating atmosphere, which enhances the expression of creative thinking in community